Multiplication of natural numbers
module elementary-number-theory.multiplication-natural-numbers where
Imports
open import elementary-number-theory.addition-natural-numbers open import elementary-number-theory.natural-numbers open import foundation.dependent-pair-types open import foundation.embeddings open import foundation.identity-types open import foundation.injective-maps open import foundation.interchange-law open import foundation.negation open import foundation.universe-levels open import group-theory.monoids open import group-theory.semigroups
Definition
Multiplication
mul-ℕ : ℕ → ℕ → ℕ mul-ℕ 0 n = 0 mul-ℕ (succ-ℕ m) n = (mul-ℕ m n) +ℕ n infix 30 _*ℕ_ _*ℕ_ = mul-ℕ mul-ℕ' : ℕ → ℕ → ℕ mul-ℕ' x y = mul-ℕ y x ap-mul-ℕ : {x y x' y' : ℕ} → x = x' → y = y' → x *ℕ y = x' *ℕ y' ap-mul-ℕ p q = ap-binary mul-ℕ p q double-ℕ : ℕ → ℕ double-ℕ x = 2 *ℕ x triple-ℕ : ℕ → ℕ triple-ℕ x = 3 *ℕ x square-ℕ : ℕ → ℕ square-ℕ x = x *ℕ x cube-ℕ : ℕ → ℕ cube-ℕ x = (square-ℕ x) *ℕ x
Properties
abstract left-zero-law-mul-ℕ : (x : ℕ) → zero-ℕ *ℕ x = zero-ℕ left-zero-law-mul-ℕ x = refl right-zero-law-mul-ℕ : (x : ℕ) → x *ℕ zero-ℕ = zero-ℕ right-zero-law-mul-ℕ zero-ℕ = refl right-zero-law-mul-ℕ (succ-ℕ x) = ( right-unit-law-add-ℕ (x *ℕ zero-ℕ)) ∙ (right-zero-law-mul-ℕ x) abstract right-unit-law-mul-ℕ : (x : ℕ) → x *ℕ 1 = x right-unit-law-mul-ℕ zero-ℕ = refl right-unit-law-mul-ℕ (succ-ℕ x) = ap succ-ℕ (right-unit-law-mul-ℕ x) left-unit-law-mul-ℕ : (x : ℕ) → 1 *ℕ x = x left-unit-law-mul-ℕ zero-ℕ = refl left-unit-law-mul-ℕ (succ-ℕ x) = ap succ-ℕ (left-unit-law-mul-ℕ x) abstract left-successor-law-mul-ℕ : (x y : ℕ) → (succ-ℕ x) *ℕ y = (x *ℕ y) +ℕ y left-successor-law-mul-ℕ x y = refl right-successor-law-mul-ℕ : (x y : ℕ) → x *ℕ (succ-ℕ y) = x +ℕ (x *ℕ y) right-successor-law-mul-ℕ zero-ℕ y = refl right-successor-law-mul-ℕ (succ-ℕ x) y = ( ( ap (λ t → succ-ℕ (t +ℕ y)) (right-successor-law-mul-ℕ x y)) ∙ ( ap succ-ℕ (associative-add-ℕ x (x *ℕ y) y))) ∙ ( inv (left-successor-law-add-ℕ x ((x *ℕ y) +ℕ y))) square-succ-ℕ : (k : ℕ) → square-ℕ (succ-ℕ k) = succ-ℕ ((succ-ℕ (succ-ℕ k)) *ℕ k) square-succ-ℕ k = ( right-successor-law-mul-ℕ (succ-ℕ k) k) ∙ ( commutative-add-ℕ (succ-ℕ k) ((succ-ℕ k) *ℕ k)) abstract commutative-mul-ℕ : (x y : ℕ) → x *ℕ y = y *ℕ x commutative-mul-ℕ zero-ℕ y = inv (right-zero-law-mul-ℕ y) commutative-mul-ℕ (succ-ℕ x) y = ( commutative-add-ℕ (x *ℕ y) y) ∙ ( ( ap (y +ℕ_) (commutative-mul-ℕ x y)) ∙ ( inv (right-successor-law-mul-ℕ y x))) abstract left-distributive-mul-add-ℕ : (x y z : ℕ) → x *ℕ (y +ℕ z) = (x *ℕ y) +ℕ (x *ℕ z) left-distributive-mul-add-ℕ zero-ℕ y z = refl left-distributive-mul-add-ℕ (succ-ℕ x) y z = ( left-successor-law-mul-ℕ x (y +ℕ z)) ∙ ( ( ap (_+ℕ (y +ℕ z)) (left-distributive-mul-add-ℕ x y z)) ∙ ( ( associative-add-ℕ (x *ℕ y) (x *ℕ z) (y +ℕ z)) ∙ ( ( ap ( ( x *ℕ y) +ℕ_) ( ( inv (associative-add-ℕ (x *ℕ z) y z)) ∙ ( ( ap (_+ℕ z) (commutative-add-ℕ (x *ℕ z) y)) ∙ ( associative-add-ℕ y (x *ℕ z) z)))) ∙ ( inv (associative-add-ℕ (x *ℕ y) y ((x *ℕ z) +ℕ z)))))) abstract right-distributive-mul-add-ℕ : (x y z : ℕ) → (x +ℕ y) *ℕ z = (x *ℕ z) +ℕ (y *ℕ z) right-distributive-mul-add-ℕ x y z = ( commutative-mul-ℕ (x +ℕ y) z) ∙ ( ( left-distributive-mul-add-ℕ z x y) ∙ ( ( ap (_+ℕ (z *ℕ y)) (commutative-mul-ℕ z x)) ∙ ( ap ((x *ℕ z) +ℕ_) (commutative-mul-ℕ z y)))) abstract associative-mul-ℕ : (x y z : ℕ) → (x *ℕ y) *ℕ z = x *ℕ (y *ℕ z) associative-mul-ℕ zero-ℕ y z = refl associative-mul-ℕ (succ-ℕ x) y z = ( right-distributive-mul-add-ℕ (x *ℕ y) y z) ∙ ( ap (_+ℕ (y *ℕ z)) (associative-mul-ℕ x y z)) left-two-law-mul-ℕ : (x : ℕ) → 2 *ℕ x = x +ℕ x left-two-law-mul-ℕ x = ( left-successor-law-mul-ℕ 1 x) ∙ ( ap (_+ℕ x) (left-unit-law-mul-ℕ x)) right-two-law-mul-ℕ : (x : ℕ) → x *ℕ 2 = x +ℕ x right-two-law-mul-ℕ x = ( right-successor-law-mul-ℕ x 1) ∙ ( ap (x +ℕ_) (right-unit-law-mul-ℕ x)) interchange-law-mul-mul-ℕ : interchange-law mul-ℕ mul-ℕ interchange-law-mul-mul-ℕ = interchange-law-commutative-and-associative mul-ℕ commutative-mul-ℕ associative-mul-ℕ is-injective-right-mul-succ-ℕ : (k : ℕ) → is-injective (_*ℕ (succ-ℕ k)) is-injective-right-mul-succ-ℕ k {zero-ℕ} {zero-ℕ} p = refl is-injective-right-mul-succ-ℕ k {succ-ℕ m} {succ-ℕ n} p = ap succ-ℕ ( is-injective-right-mul-succ-ℕ k {m} {n} ( is-injective-right-add-ℕ ( succ-ℕ k) ( ( inv (left-successor-law-mul-ℕ m (succ-ℕ k))) ∙ ( ( p) ∙ ( left-successor-law-mul-ℕ n (succ-ℕ k)))))) is-injective-right-mul-ℕ : (k : ℕ) → is-nonzero-ℕ k → is-injective (_*ℕ k) is-injective-right-mul-ℕ k H p with is-successor-is-nonzero-ℕ H ... | pair l refl = is-injective-right-mul-succ-ℕ l p is-injective-left-mul-succ-ℕ : (k : ℕ) → is-injective ((succ-ℕ k) *ℕ_) is-injective-left-mul-succ-ℕ k {m} {n} p = is-injective-right-mul-succ-ℕ k ( ( commutative-mul-ℕ m (succ-ℕ k)) ∙ ( p ∙ commutative-mul-ℕ (succ-ℕ k) n)) is-injective-left-mul-ℕ : (k : ℕ) → is-nonzero-ℕ k → is-injective (k *ℕ_) is-injective-left-mul-ℕ k H p with is-successor-is-nonzero-ℕ H ... | pair l refl = is-injective-left-mul-succ-ℕ l p is-emb-left-mul-ℕ : (x : ℕ) → is-nonzero-ℕ x → is-emb (x *ℕ_) is-emb-left-mul-ℕ x H = is-emb-is-injective is-set-ℕ (is-injective-left-mul-ℕ x H) is-emb-right-mul-ℕ : (x : ℕ) → is-nonzero-ℕ x → is-emb (_*ℕ x) is-emb-right-mul-ℕ x H = is-emb-is-injective is-set-ℕ (is-injective-right-mul-ℕ x H) is-nonzero-mul-ℕ : (x y : ℕ) → is-nonzero-ℕ x → is-nonzero-ℕ y → is-nonzero-ℕ (x *ℕ y) is-nonzero-mul-ℕ x y H K p = K (is-injective-left-mul-ℕ x H (p ∙ (inv (right-zero-law-mul-ℕ x)))) is-nonzero-left-factor-mul-ℕ : (x y : ℕ) → is-nonzero-ℕ (x *ℕ y) → is-nonzero-ℕ x is-nonzero-left-factor-mul-ℕ .zero-ℕ y H refl = H (left-zero-law-mul-ℕ y) is-nonzero-right-factor-mul-ℕ : (x y : ℕ) → is-nonzero-ℕ (x *ℕ y) → is-nonzero-ℕ y is-nonzero-right-factor-mul-ℕ x .zero-ℕ H refl = H (right-zero-law-mul-ℕ x)
We conclude that if .
is-one-is-right-unit-mul-ℕ : (x y : ℕ) → (succ-ℕ x) *ℕ y = succ-ℕ x → is-one-ℕ y is-one-is-right-unit-mul-ℕ x y p = is-injective-left-mul-succ-ℕ x (p ∙ inv (right-unit-law-mul-ℕ (succ-ℕ x))) is-one-is-left-unit-mul-ℕ : (x y : ℕ) → x *ℕ (succ-ℕ y) = succ-ℕ y → is-one-ℕ x is-one-is-left-unit-mul-ℕ x y p = is-injective-right-mul-succ-ℕ y (p ∙ inv (left-unit-law-mul-ℕ (succ-ℕ y))) is-one-right-is-one-mul-ℕ : (x y : ℕ) → is-one-ℕ (x *ℕ y) → is-one-ℕ y is-one-right-is-one-mul-ℕ zero-ℕ zero-ℕ p = p is-one-right-is-one-mul-ℕ zero-ℕ (succ-ℕ y) () is-one-right-is-one-mul-ℕ (succ-ℕ x) zero-ℕ p = is-one-right-is-one-mul-ℕ x zero-ℕ p is-one-right-is-one-mul-ℕ (succ-ℕ x) (succ-ℕ y) p = ap ( succ-ℕ) ( is-zero-right-is-zero-add-ℕ (x *ℕ (succ-ℕ y)) y ( is-injective-succ-ℕ p)) is-one-left-is-one-mul-ℕ : (x y : ℕ) → is-one-ℕ (x *ℕ y) → is-one-ℕ x is-one-left-is-one-mul-ℕ x y p = is-one-right-is-one-mul-ℕ y x (commutative-mul-ℕ y x ∙ p) neq-mul-ℕ : (m n : ℕ) → ¬ (succ-ℕ m = (succ-ℕ m) *ℕ (succ-ℕ (succ-ℕ n))) neq-mul-ℕ m n p = neq-add-ℕ ( succ-ℕ m) ( ( m *ℕ (succ-ℕ n)) +ℕ n) ( ( p) ∙ ( ( right-successor-law-mul-ℕ (succ-ℕ m) (succ-ℕ n)) ∙ ( ap ((succ-ℕ m) +ℕ_) (left-successor-law-mul-ℕ m (succ-ℕ n)))))
The multiplicative monoid ℕ*
ℕ*-Semigroup : Semigroup lzero pr1 ℕ*-Semigroup = ℕ-Set pr1 (pr2 ℕ*-Semigroup) = mul-ℕ pr2 (pr2 ℕ*-Semigroup) = associative-mul-ℕ ℕ*-Monoid : Monoid lzero pr1 ℕ*-Monoid = ℕ*-Semigroup pr1 (pr2 ℕ*-Monoid) = 1 pr1 (pr2 (pr2 ℕ*-Monoid)) = left-unit-law-mul-ℕ pr2 (pr2 (pr2 ℕ*-Monoid)) = right-unit-law-mul-ℕ